Modern Music Technology at School - Golob, Katarina (Širjenje obzorij o poučevanju glasbe, 2025)
The rapid development of information and communication technology has profoundly impacted the process of learning music. One notable change is that the teacher is no longer the sole source of information but rather a guide, enabling students to access and manage their own learning processes. This chapter explores the various tools that modern music technology offers in schools. These include digital audio workstations (DAWs), apps for iPads, and sound recording technologies that allow students to develop their musical skills in an interactive way. Mobile devices, such as iPads, and apps like LoopsequeKids and Moozart enable young learners to explore, create music, and express their musical ideas. Significantly, modern technology in education fosters creative thinking and musical creativity, positively influencing the learning experience and increasing student engagement.